Artificial Intelligence and Mental Health - Inamdar, Harshada Joshi (International Journal of Nursing Research, 2024)
In addition to identifying challenges and prospects for such application, this paper intends to present significant implementation science ideas that may be pertinent to comprehending and aiding artificial intelligence (AI) deployment in mental health care. This paper provides an overview of AI technology in modern mental health care and evaluates recent research developments, with a focus on the developing field of digital psychiatry. AI application in psychiatry to improve our knowledge, diagnosis, and treatment of mental diseases; to address concerns with availability, appeal, and accessibility of mental health-care services. Nursing staff members and other medical professionals, who operate in clinical settings, such as mental health facilities, stand to gain significantly from AI’s potential to increase workplace productivity and efficiency. Using the phrases “AI in mental health,” “diagnosis of mental health disorders,” “artificial intelligence,” and “deep learning,” we searched PubMed psychological testing and psychotherapy are being impacted by cutting-edge technologies such as artificial and Web of science. The research covered in this overview of the literature discusses how intelligence. This is a survey article, hence not applicable. The advantages and moral dilemmas associated with the use of AI in psychiatry are outweighed by its potential uses. More research and advancement are needed to get past these obstacles and guarantee the ethical and safe integration of AI in the psychiatric sector. By doing this, AI can significantly advance both long-term outcomes and the organization of mental health services.